Efficacy of Commercial Products on Growth Performance of Nursery Pigs Fed Diets with Fumonisin-Contaminated Corn - Z. X. Rao; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband; H. Calderon Cartagena (Kansas Agricultural Experiment Station Research Reports, 2019)
Two experiments were conducted to determine the efficacy of various commercial products on growth performance of 20- to 50-lb nursery pigs fed diets high in fumonisin (FUM) concentration. In Exp. 1, a total of 350 pigs (241 × 600; DNA, Columbus, NE; initially 21.8 lb) were used. There were 5 pigs per pen and 14 replicates per treatment. After weaning, pigs were fed common diets for 21 d before the experiment started. Five dietary treatments were utilized and consisted of a positive control (low FUM), a negative control (approximately 50 to 60 ppm of FUM), and 3 other treatments as negative control with one of 3 different commercial products (Kallsil Dry, Kemin Industries Inc., Des Moines, IA; Feed Aid Wide Spectrum, NutriQuest, Mason City, IA; Biofix Select Pro, Biomin America Inc., Overland Park, KS). Diets were fed in mash form for 14 d and followed with a low FUM mash diet for 13 d as a post-treatment period. For the 14-d treatment period, pigs fed the high FUM negative control, or high FUM diets with Kallsil Dry or Feed Aid Wide Spectrum had decreased (P<0.05) average daily gain (ADG), average daily feed intake (ADFI), and d 14 body weight (BW), and poorer (P<0.05) feed efficiency (F/G) compared to the positive control and treatment with Biofix Select Pro. Pigs fed the high FUM diet with Biofix Select Pro had similar performance to pigs fed the low FUM diet. During the 13-day post-treatment period, pigs previously fed the high FUM negative control, or high FUM diets with Kallsil Dry or Feed Aid Wide Spectrum had improved F/G compared with pigs previously fed the low FUM diet or high FUM diet with Biofix Select Pro. Although the performance of the pigs previously fed the high FUM diets without additive or with Kallsil Dry or Feed Aid Wide Spectrum improved, their d 27 BW were still lower (P<0.05) compared to pigs previously fed the positive control and high FUM diet with Biofix Select Pro. In Exp. 2, a total of 300 pigs (241 × 600; DNA; initially 23.0 lb) were used. Procedures were similar to Exp. 1 except there were 12 replicate pens per treatment and high FUM diets contained 30 ppm FUM, and experimental diets were fed for 28 d. Similar to Exp. 1, for the 28-d treatment period, pigs fed the high FUM negative control, or high FUM diets with Kallsil Dry or Feed Aid Wide Spectrum had decreased (P<0.05) ADG, ADFI, and d 28 BW, and poorer (P<0.05) F/G compared to the positive control and treatment with Biofix Select Pro. Pigs fed the high FUM diet with Biofix Select Pro had similar performance to pigs fed the low FUM diet. In summary, adding Biofix Select Pro to diets containing 30 to 50 ppm of FUM appeared to mitigate the negative effects of FUM, while Kallsil Dry and Feed Aid Wide Spectrum did not influence pig performance.
Keywords: corn; fumonisin (FUM); nursery; pigs